Analisis Sistem Antrian pada Pelayanan Help Desk UPT TIK Institut Teknologi Sumatera Menggunakan Teori Antrian - Dwi Rianti; Utriweni Mukhaiyar; Lutfi Mardianto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2022)
The analysis of the queuing system at the Help Desk service of the UPT TIK Institut Teknologi Sumatera includes the number of ticket arrivals, the average length of service time, and the number of service facilities (admin). The data for the number of Help Desk tickets are Poisson distributed and the service time is the Exponential distribution. The size of the steady-state in the service has a value of so that an analysis of the performance size of the queue system can be carried out. The data used in the study are Help Desk ticket data for the period November 2020-February 2021. The results obtained indicate that the queue model for the Help Desk service can be added to the server (admin). The addition of a server in the service can reduce the workload significantly. The queue model that can be applied is M/M/3:FCFS/∞/∞ by adding one server (admin), from the previous model, namely M/M/2:FCFS/∞/∞.